English English: English - Brunnbauer, Ulf (Ревија за социјална политика/Journal of Social Policy, 2025)
This article results from an exploration in the production of knowledge about old age in socialist Yugoslavia. It particularly discusses the relationship between research and policy making, highlighting two contradictory tendencies: on the one hand, government bodies in Yugoslavia commissioned and funded substantial research in the social problems of old people, starting in the mid-1960s. On the other hand, policy responses remained deficient. I argue that one reason was the geographic concentration of problems of old age in villages, which were generally neglected by the government; this was manifest in the lack of pension coverage for private farmers and often miserable living conditions. My article is based on a close reading of Yugoslav social-science research on old people and on the analysis of archival documents about social policies in this arena. There is a particular focus on the Socialist Republic of Macedonia, where large-scale surveys of the situation of old people were carried out in the 1970s and 1980s, but where the government response remained insufficient. By the late 1980s, experts seemed to have given up the hope that their research might help to improve alleviating the lot of old people. My contribution is also understood as a rediscovery of a rich research tradition that fell into oblivion during the wars of the 1990s. Yet if we want to understand the dynamics of social inequality in Yugoslavia – as one of the reasons of its dissolution – we should listen to those contemporaneous voices.